Clinical efficacy of bioactive restorative materials in controlling secondary caries: a systematic review and network meta-analysis - Noeleni Souza Pinto; Gabriela Rebouças Jorge; Jader Vasconcelos; Livia Fernandes Probst; Alessandro Diogo De-Carli; Andrea Freire (BMC, 2023)
Abstract Background This systematic review and network meta-analysis aimed to compare the clinical efficacy of bioactive and conventional restorative materials in controlling secondary caries (SC) and to provide a classification of these materials according to their effectiveness. Methods A search was performed in Pubmed, Web of Science, Embase, BBO, Lilacs, Cochrane Library, Scopus, IBECS and gray literature. Clinical trials were included, with no language or publication date limitations. Paired and network meta-analyses were performed with random-effects models, comparing treatments of interest and classifying them according to effectiveness in the permanent and deciduous dentition and at 1-year or 2/more years of follow-up. The risk of bias and certainty of evidence were evaluated. Results Sixty-two studies were included in the qualitative syntheses and 39 in the quantitative ones. In permanent teeth, resin composite (RC) (RR = 2.00; 95%CI = 1.10, 3.64) and amalgam (AAG) (RR = 1.79; 95%CI = 1.04, 3.09) showed a higher risk of SC than Glass Ionomer Cement (GIC). In the deciduous teeth, however, a higher risk of SC was observed with RC than with AAG (RR = 2.46; 95%CI = 1.42, 4.27) and in GIC when compared to Resin-Modified Glass Ionomer Cement (RMGIC = 1.79; 95%CI = 1.04, 3.09). Most randomized clinical trials studies showed low or moderate risk of bias. Conclusion There is a difference between bioactive restorative materials for SC control, with GIC being more effective in the permanent teeth and the RMGIC in the deciduous teeth. Bioactive restorative materials can be adjuvants in the control of SC in patients at high risk for caries.